ANALYSIS OF ADVERSE DRUG REACTIONS (ADRs) AND THEIR SEVERITY IN BREAST CANCER PATIENTS TREATED WITH THE DOCETAXEL-DOXORUBICIN REGIMEN AT SULTAN AGUNG ISLAMIC HOSPITAL - Setiaji, Muh Maskur; Cholisoh, Zakky (Jurnal Farmasi Sains dan Praktis, 2025)
The use of the docetaxel-doxorubicin regimen in breast cancer treatment has been associated with Adverse Drug Reactions (ADRs). This study aims to analyze the occurrence of ADRs and their severity in breast cancer patients undergoing therapy with the docetaxel-doxorubicin regimen at the hospital. The research design employed a quantitative cross-sectional approach, and purposive sampling was used as the sampling technique. Six primary Adverse Drug Reactions (ADRs) were identified among breast cancer patients undergoing chemotherapy with the docetaxel-doxorubicin regimen: nausea (21,32%), anemia (13,71%), peripheral neuropathy (7,45%), alopecia (23,01%), cardiac disorders (7,11%), and anorexia (9.81%). Breast cancer patients treated with the docetaxel doxorubicin regimen experienced various levels of ADR severity. Among the 591 adverse drug reaction (ADR) incidents recorded, the majority (55.6%) were classified as mild (severity level 1), with nausea reported as the most common side effect. At severity level 2 (moderate), alopecia was predominant, while at severity level 3 (severe), anemia was the most common reaction. There were no ADR incidents reported at severity levels 4 and 5